MOTIVATIONAL FACTORS AND THE ELDERLY IN LABOR ACTIVITIES - Trigueiro, Francisco Mirialdo Chaves; Bitante, Alessandra Preto; Kubo, Edson Keyso de Miranda; Oliva, Eduardo de Camargo (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
The aging population is something prominent around the world and in Brazil assessments show that by 2050 the population over 60 years old will be three times greater than in 2015. Within the context of labor activity, research indicates that the elderly who continue to work are healthier, happier and more active, developing fewer diseases and collaborating more with society. This study relies on a descriptive research of quantitative nature, based on field survey with 270 elderly in São Caetano do Sul city, that holds a programa towards elderly called “Experience in Action”. It was observed the existence of two clusters of aging people, characterized as more solitary and less solitary, that emphasize the feeling of productivity, increase of income, social valorization, the application of acquired knowledge, self-esteem and well-being and taste for work.